Sources of fine particulate matter in personal exposures and residential indoor, residential outdoor and workplace microenvironments in the Helsinki phase of the EXPOLIS study - Koistinen, Kimmo J.; Edwards, Rufus D.; Mathys, Patrick; Ruuskanen, Juhani; Künzli, Nino; Jantunen, Matti J. (Scandinavian Journal of Work, Environment & Health, 2004)
' ' OBJECTIVES ': 'This study assessed the source contributions to the mass concentrations of fine particles (PM2.5) in personal exposures and in residential indoor, residential outdoor, and workplace indoor microenvironments of the nonsmoking adult population unexposed to environmental tobacco smoke in Helsinki, Finland. ' ' METHODS ': 'The elemental composition of 48-hour personal exposure and residential indoor, residential outdoor, and workplace indoor PM2.5 was analyzed by energy-dispersive X-ray fluorescence spectrometry for 76 participants not exposed to environmental tobacco smoke and 102 participating residences with no smoking in Helsinki as a part of the EXPOLIS study. Subsequently, a principal component analysis was used to identify the emission sources of PM2.5-bound elements and black smoke in each microenvironment, and this information was used to identify the corresponding sources in personal exposures. Finally, source reconstruction was done to determine the relative contributions of each source type to the total PM2.5 mass concentrations. ' ' RESULTS ': 'Inorganic secondary particles, primary combustion, and soil were the dominant source types for the PM2.5 mass concentration in all the microenvironments and personal exposures. The ratio of the residential indoor-to-outdoor PM2.5 concentration was close to unity, but the corresponding elemental ratios and source contributions varied. Resuspension of soil dust tracked indoors was a much larger contributor to residential and workplace indoor PM2.5 than soil dust to residential outdoor PM2.5. Source contributions to personal PM2.5 exposures were best approximated by data from residential and workplace indoor microenvironments. ' ' CONCLUSIONS ': 'Population exposure assessment of PM2.5, based on outdoor fixed-site monitoring, overestimates exposures to outdoor sources like traffic and long-range transport and does not account for the contribution of significant indoor sources.
Keywords: elemental composition; expolis study; exposure; fine particles; Helsinki; indoor; long-range transport; microenvironment; outdoor microenvironment; particulate matter; personal exposure; principal component analysis; soil; source apportionment; source reconstruction; traffic; workplace